Hepatoprotective effect of edible Oyster mushroom Pleurotus cornucopiae against Sodium Arsenite induced hepatotoxicity in rats - Arun Kumar,; Swapnil Suman,; Ranjit Kumar,; JK Singh,; Mohammad Ali, (International Journal of Phytomedicine, 2014)
Arsenic poisoning in ground water had been major challenge for the mankind in arsenic hit areas. In India, this problem is a big alarm in the entire Gangetic belt. The arsenic poisoning through drinking water has caused lots of health hazards to humans especially related hepato-biliary. This present study was carried out to investigate the therapeutic role of the ethanolic extract of Pleurotus cornucopiae on Sodium Arsenite induced hepatotoxicity in rats. Sodium Arsenite at the dose of 8mg/kg-1 body weight orally caused liver damage in rats as manifested by the significant rise in serum levels of Serum Glutamic Pyruvate Transaminase (SGPT), Serum Glutamate Oxalate Transaminase (SGOT), Alkaline Phosphatase (ALP) and Bilirubin levels compared with control. Oral administration of 400mg extracts of P. cornucopiae (/kg) for 30 days to Sodium Arsenite treated rats showed significant ameleoration in these levels. Thus, the entire study reveals that ethanolic extract of P. cornucopiae at the dose of 400 mg/kg-1 body weight shows hepatoprotective effect against arsenic induced toxicity.